Zdravljenje kroničnega srčnega popuščanja z resinhronizacijskim spodbujevalnikom - Geršak, Borut (Zdravniški vestnik, 2005)
Chronic heart fuilure due to systolic dysfunction has been treated pharmacologically by the extensitve use of ACE inhibitors, beta blockers, spyronolactone and digoksin improving morbidity, mortality and the quality of life as well as decreasing hospitalisation rate in the last decade. However, despite all the endeavors to optimize pharmacological treatment the mortality of the described syndrom remains unreasonably high and many patients sufferly expressed symptoms that considerably affect their quality of life. Thus, noveltreatment modalities are being sought continuously and their is one, namely cardiac resynchronisation therapy which has gained increasing interst in the last couple of years.
Keywords: Defibrilatorji, vsadek; Defibrillators, Implantable; Heart Failure, Congestive; Srce, odpoved kongestivna